Freshwater ice as habitat: partitioning of phytoplankton and bacteria between ice and water in central European reservoirs - McKay, Robert M L; Prášil, Ondrej; Pechar, Libor; Lawrenz, Evelyn; Rozmarynowycz, Mark J; Bullerjahn, George S (Environmental microbiology reports, 2015)
Abundant phytoplankton and bacteria were identified by high-throughput 16S rRNA tag Illumina sequencing of samples from water and ice phases collected during winter at commercial fish ponds and a sand pit lake within the UNESCO Třeboň Basin Biosphere Reserve, Czech Republic. Bacterial reads were dominated by Proteobacteria and Bacteroidetes. Despite dominance by members of just two phyla, UniFrac principal coordinates analysis of the bacterial community separated the water community of Klec fish pond, as well as the ice-associated community of Klec-Sand Pit from other samples. Both phytoplankton and cyanobacteria were represented with hundreds of sequence reads per sample, a finding corroborated by microscopy. In particular, ice from Klec-Sand Pit contained high contributions from photoautotrophs accounting for 25% of total reads with reads dominated by single operational taxonomic units (OTUs) of the cyanobacterium Planktothrix sp. and two filamentous diatoms. Dominant OTUs recovered from ice were largely absent (< 0.01%) from underlying water suggestive of low floristic similarity of phytoplankton partitioned between these phases. Photosynthetic characterization of phototrophs resident in water and ice analysed by variable chlorophyll a fluorescence showed that communities from both phases were photosynthetically active, thus supporting ice as viable habitat for phytoplankton in freshwater lakes and reservoirs.
Keywords: Phytoplankton; Seasons; Ponds; Fresh Water; ekosystém; Bacteria; biodiverzita; Česká republika; Ice; sladká voda; rybníky; Czech Republic; fotosyntéza; led; Photosynthesis; mikrobiologie vody; fytoplankton; Biodiversity; Water Microbiology; Ecosystem; roční období